(untitled) (Research, Society and Development, 2025)
The role of leukocytes in semen remains controversial, with both beneficial effects, such as the removal of microorganisms and abnormal sperm, and harmful effects, including reactive oxygen species (ROS) production and reduced fertility potential. Research on this topic in farm animals is limited. This study investigated correlations between differential leukocyte counts in bull semen and sperm parameters, both fresh and post-thaw. A total of 44 ejaculates from 36 adult bulls were collected using the artificial vagina method. Semen cytology was performed with Diff-Quick staining, and leukocytes were quantified under an optical microscope. Sperm parameters analyzed included ejaculate volume, motility (fresh and post-thaw), concentration, and morphology (major, minor, and total defects). Lymphocytes predominated (82%), followed by macrophages (13%), neutrophils (4%), and eosinophils (1%). Neutrophils showed weak negative correlations with major defects (r = -0.36, P = 0.027) and total defects (r = -0.328, P = 0.047), as well as a moderate negative correlation with post-thaw motility (r = -0.515, P = 0.0012) in Spearman’s correlation analysis. In contrast, lymphocytes, macrophages, and eosinophils showed no significant correlations with sperm parameters. These findings suggest that among leukocyte populations, only neutrophils negatively impact sperm morphology in fresh semen and motility in thawed semen.